An NGS-based microhaplotype system with high polymorphism for forensic DNA mixtures analysis. (December 2022) - Tan, Mengyu; Xue, Jiaming; Zhang, Ranran; Jian, Hui; Xiao, Yuanyuan; Liu, Guihong; Zheng, Yazi; Wu, Qiushuo; Qu, Shengqiu; Liang, Weibo
Abstract: Microhaplotype is a novel genetic marker characterized by high polymorphism and short amplicon, which have a powerful potential in mixture deconvolution. The previous microhaplotype only contained single nucleotide polymorphisms (SNPs), we suggested two or more closely linked SNPs/insertion and deletion polymorphisms (Indels) associated in multiple allelic combinations within 300 bp can be defined as generalized microhaplotypes to increase the number of candidate loci and polymorphism. We developed a system consisting of two groups of 62 and 71 microhaplotypes with high polymorphism based on the Next Generation Sequencing (NGS) platform for the mixture analysis. Our results indicated that the average Ae values of the two groups were 7.36 and 5.35, and the number of microhaplotypes with Ae greater than 5 was 44 and 32, respectively. Artificial multi-person and imbalanced mixtures were also tested to explore preliminarily the performance of this system showed that it will help detect and analyze the DNA mixtures more effectively.